Large multicentre pilot randomised controlled trial testing a low-cost, tailored, self-help smoking cessation text message intervention for pregnant smokers (MiQuit) - Naughton, Felix; Cooper, Sue; Foster, Katharine; Emery, Joanne; Leonardi-Bee, Jo; Sutton, Stephen; Jones, Matthew; Ussher, Michael; Whitemore, Rachel; Leighton, Matthew; Montgomery, Alan; Parrott, Steve; et al. (Wiley, 2017)
Aims: To estimate the effectiveness of pregnancy smoking cessation support delivered by SMS text message and key parameters needed to plan a definitive trial. Design: Multicentre, parallel-group, single-blinded, individual randomised controlled trial Setting: 16 antenatal clinics in England. Participants: 407 participants were randomised to the intervention (n=203) or usual care (n=204). Eligible women were <25 weeks gestation, smoked at least 1 daily cigarette (> 5 pre-pregnancy), were able to receive and understand English SMS texts and were not already using text-based cessation support. Intervention: All participants received a smoking cessation leaflet; intervention participants also received a 12-week programme of individually-tailored, automated, interactive, self-help smoking cessation text messages (MiQuit). Outcome Measurements: Seven smoking outcomes including validated continuous abstinence from 4 weeks post-randomisation until 36 weeks gestation, design parameters for a future trial and cost-per-quitter. Findings: Using the validated, continuous abstinence outcome, 5.4% (11/203) of MiQuit participants were abstinent versus 2.0% (4/204) of usual care participants (odds ratio [OR] 2.7, 95% confidence interval [CI] 0.93 to 9.35). The Bayes Factor for this outcome was 2.23. Completeness of follow up at 36 weeks gestation was similar in both groups; provision of self-report smoking data was 64% (MiQuit) and 65% (usual care) and abstinence validation rates were 56% (MiQuit) and 61% (usual care). The incremental cost-per-quitter was £133.53 (95% CI -£395.78 to £843.62). Conclusions: There was some evidence, though not conclusive, that a text messaging programme may increase cessation rates in pregnant smokers when provided alongside routine NHS cessation care.